Improving Product Quality under the Application of Lean Accounting Tools within the Behavioral Approach - Alotaibi, Dirar Abdulhameed Altoum; Al-Kawaz, Salah Mahdi Jawad; Abbas, Ali Abdulhassan (International Journal of Economics and Financial Issues, 2021)
The current research aims to study the importance of applying lean accounting technology with its important tools such as (value stream, points box, continuous improvement) and pointing to the role of correct behaviors by the decision maker that helps in making the right decision in improving the quality of the product and its reflection on reducing its cost Reducing waste and wasting of resources, meeting customer requirements, and trying to apply it in one of the factories of the Southern Cement Company represented by the Kufa Cement Factory, the sample of the research, and to achieve this goal, it was adopted in the application of lean accounting tools on the laboratory data obtained by the result of coexistence field Take a look at the laboratory records for the sample. The researchers reached several conclusions, the most important of which is that the research sample represented by the Kufa Cement Factory is far from the concept of lean accounting, including the important tools and what it reflects in its application of a role in improving the quality of the product, including this concept holds multiple meanings, in addition to not paying enough attention to achieve customer satisfaction Which is one of the important constituents of the newly targeted, because the customer has become the starting point for the business of economic units and the basis of their survival in the market. Also, not taking into consideration the behavior of the decision-maker, which may not be in harmony with the organization and reflected in making weak decisions that affect the concept of lean accounting. Keywords: Product Quality, Lean Accounting Tools, Behavioral Approach JEL Classifications: M41, L15, M11 DOI: https://doi.org/10.32479/ijefi.10975